2014
DOI: 10.1371/journal.ppat.1004507
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-Dorsal Pathway Is Required for Resistance to Viral Oral Infection in Drosophila

Abstract: Pathogen entry route can have a strong impact on the result of microbial infections in different hosts, including insects. Drosophila melanogaster has been a successful model system to study the immune response to systemic viral infection. Here we investigate the role of the Toll pathway in resistance to oral viral infection in D. melanogaster. We show that several Toll pathway components, including Spätzle, Toll, Pelle and the NF-kB-like transcription factor Dorsal, are required to resist oral infection with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
245
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(257 citation statements)
references
References 104 publications
(133 reference statements)
10
245
2
Order By: Relevance
“…The role of this gene in antiviral defence has been supported by a study showing that a treatment with the neonicotinoid insecticide clothianidin, that indirectly targets the same gene, results in high levels of DWV replication (Di Prisco et al, 2013). Interestingly, the role of dorsal in antiviral defence does not seem to be restricted to honey bees, since it has been shown that the Toll-Dorsal Pathway is required for resistance to viral oral infection in the fruit fly as well (Ferreira et al, 2014). The observed effect on dorsal appears to be particularly interesting in view of the increased viral infection in mite infested bees confirmed in this study.…”
Section: Zanni Et Al / Insect Biochemistry and Molecular Biology mentioning
confidence: 99%
“…The role of this gene in antiviral defence has been supported by a study showing that a treatment with the neonicotinoid insecticide clothianidin, that indirectly targets the same gene, results in high levels of DWV replication (Di Prisco et al, 2013). Interestingly, the role of dorsal in antiviral defence does not seem to be restricted to honey bees, since it has been shown that the Toll-Dorsal Pathway is required for resistance to viral oral infection in the fruit fly as well (Ferreira et al, 2014). The observed effect on dorsal appears to be particularly interesting in view of the increased viral infection in mite infested bees confirmed in this study.…”
Section: Zanni Et Al / Insect Biochemistry and Molecular Biology mentioning
confidence: 99%
“…However, it remains to be determined how flies succumb to DCV infection. DCV infects a variety of tissues and organs in Drosophila, including the fat body, periovarial sheath, trachea, muscle, and digestive tract (31,44,62,67,68). A recent report argued that alteration in a variety of physiological and metabolic phenomena is related to the death of DCV-infected flies (69).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported changes in the morphology of flies (i.e., abdominal swelling and crop enlargement) upon infection with DCV (31,62). We wondered whether such morphological changes are due to the expansion of infection.…”
Section: Exaggeration Of Morphological Change In Dcv-infected Flies Bmentioning
confidence: 97%
See 1 more Smart Citation
“…Both humoral (23) and cellular (19) immunity play roles in the protection of flies against viral infection, including that with DCV. Therefore, we compared the amounts of the mRNAs of antimicrobial peptides and Hours post-infection when flies start to die (onset) and all flies are dead (extinct) are shown as a summary of the data from three independent experiments with two different viral doses.…”
Section: Increases In the Level Of The Mrnas Of Immunityrelated Protementioning
confidence: 99%